2010
DOI: 10.4155/fmc.10.217
|View full text |Cite
|
Sign up to set email alerts
|

Gram-Scale Synthesis of the P38α MAPK-Inhibitor VX-745 for Preclinical Studies into Werner Syndrome

Abstract: This method delivers the p38 inhibitor VX-745 in sufficient quantities for preclinical studies to rescue the aging phenotype in Werner syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…All three p38 inhibitors reduced the level of p-p38 in GM18366 cells to some extent but didn’t abolish it (Figure 2A). The ability of p38 inhibitors to partially prevent p38 activation has been reported previously for VX-745 and SB203580 at the concentrations used here (33). BIRB 796 is reported to completely prevent phosphorylation of p38 at 10 µM but not at 1 µM (32,37); thus, it may be expected that BIRB 796 would only partially prevent p38 activation at the concentration of 2.5 µM used here.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…All three p38 inhibitors reduced the level of p-p38 in GM18366 cells to some extent but didn’t abolish it (Figure 2A). The ability of p38 inhibitors to partially prevent p38 activation has been reported previously for VX-745 and SB203580 at the concentrations used here (33). BIRB 796 is reported to completely prevent phosphorylation of p38 at 10 µM but not at 1 µM (32,37); thus, it may be expected that BIRB 796 would only partially prevent p38 activation at the concentration of 2.5 µM used here.…”
Section: Resultssupporting
confidence: 80%
“…BIRB 796 and VX-745 were synthesized according to Bagley and colleagues (32,33). For experiments using inhibitors, growth medium was supplemented with SB203580 and BIRB 796 at 2.5 µM and VX-745 at 0.5 µM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it was found that pamapimod can clearly alleviate various rheumatoid arthritis symptoms when coadministered with methotrexate [136]. Besides, there are still many other inhibitors which are ongoing clinical trials as summarized in Table 4 [137140]. …”
Section: Development Of P38-targeted Drugs As New Anti-inflammatormentioning
confidence: 99%
“…The role of stress signaling in Werner syndrome cells has been investigated using a range of small molecule inhibitors ( Figure 1 ) of p38 MAPK [ 16 ], including SB203580 [ 12 , 17 , 18 ], VX-745 [ 19 , 20 , 21 ], RO3201195 [ 22 , 23 ], UR-13756 [ 24 ], and BIRB 796 [ 25 ], to study the link between replicative senescence in vitro and in vivo pathophysiology. WS fibroblasts treated with a p38 inhibitor display an unexpected reversal of the accelerated aging phenotype [ 12 ] and, as such, this may provide a suitable model for future therapeutic interventions designed to combat the aging process itself [ 12 , 26 ].…”
Section: Introductionmentioning
confidence: 99%